PENANAMAN PENDIDIKAN KARAKTER RELIGIUS PESERTA DIDIK SEKOLAH DASAR - Rokhimah, Nur Arfiyah Ghina; Herianingtyas, Nur Luthfi Rizqa (LPPM Universitas Bina Bangsa, 2023)
Religious values are very important in education, especially for strengthening the character of children in elementary schools. Thus, the religious values applied to elementary school children greatly affect the morale of these children. This study aims to find out and describe how the formation of religious character in a general elementary school, namely SDN Pisangan 03 which lives in Pisangan Village, East Ciputat District, South Tangerang City, Banten Province. Basically, this research uses a qualitative descriptive method. In data collection techniques using techniques by means of surveys, observations and literature reviews as well as studying relevant theoretical perspectives to facilitate understanding of the phenomena that researchers want to study, namely collecting reference sources from both books and journals. The published topics are related to the research focus that is further explored by researchers, namely religious character education. The conclusion of this study is that SDN Pisangan 03 has started to instill character in students by habituating them in the school environment from coming to school